Pengaruh Metode Pengajaran Kreatif terhadap Motivasi Belajar Siswa dalam Pelajaran Matematika SDN Kranji II - Alvianda Bunga Ayumi; Ferianto Ferianto (Fakultas Agama Islam Universitas Singperbangsa Karawang, 2023)
This article discusses how much influence a simple and easy-to-understand teaching method has on students' motivation to like math well. Basically, there are a lot of students who don't like math because it is difficult and requires effective teaching to understand it, math is one of the subjects that uses logic, critical, and rational in solving its problems, therefore it requires high concentration to understand it, besides that the method in teaching is also very influential on students like what is effective and makes students like math subjects, especially factors that can influence students towards math subjects. A little bit of what we see now is that many teachers only rely on the teaching system without knowing what kind of methods are good for students, and that has a very bad effect when students hear about math lessons. Why do many dislike math, what factors make students dislike math, in this article will answer these questions with all the learning and research.